Dilemmas of interpreting folk culture in the cross-border regions of Hajdú-Bihar and Bihor counties - Horváth, Péter (Acta Agraria Debreceniensis, 2015)
Identity connected to the dwelling-place has been, and still is, shaped by many (regional, natural, cultural, administrative, and historical) factors. The Euro region of Hajdú-Bihar–Bihor can be considered as a sort of transitional region, which has a strong impact on the cultural identity of both individuals and small communities. The identity construction of local inhabitants, however, does not necessarily follow the different geographical, ethnographical and historical borders of subregions. As a result, several transitional zones exist, which are now divided by a national border, too. Consequently, although many research theories and aspects have been conceived, no uniform method of approach has been created, which would define exactly the classification of folk culture in terms of small, medium and large region. The present short study examines problems posed by this question.